Pornography Behavior of Junior High School Student - Rika Hardani; Dwi Hastuti; Lilik Noor Yuliati (Journal of Child Development Studies, 2018)
Abstract. The purpose of research is to identify the pornography behavior ofJunior High School student. We used cross-sectional study as research design. Locations were taken by purposive in South Tangerang city conducted in four junior high school. Schools were selected purposively based on the recommendation of the Ministry of Education in South Tangerang. Participants used are 600 children, boys 278 and girls 322 children. Data were collected by questionnaires filled out by participants.The pornography  behavior of junior high school student that have been studied are viewing  pornographic web, reading books or comics that contain pornographic pictures, hearing or saying things porn, think of things related to pornography. This study also want to know the things that encourage the child to thepornographic behavior and the diference pornography behavior between boys and girls.The results showed that the behavior of pornography on boys is higher than girls. The pornography behavior on boys and girls there are no statistically significant differences (p value = 0:03 *, p <0.05).Key words :pornography behavior, junior high school student, internet influence